A giant malignant phyllodes tumor of breast post mastectomy with metastasis to stomach manifesting as anemia: a case report and review of literature - Hui-Pu Liu; Wen-Yen Chang; Chin-Wen Hsu; Shan-Tao Chien; Zheng-Yi Huang; Wen-Ching Kung; Ping-Hung Liu (BMC Surgery, 2020)
Abstract Background Phyllodes tumors (PTs) are well known for local recurrence and progression. Less than 10% of these tumors grow larger than 10 cm. Distant metastases have been reported in up to 22% of malignant PTs, with most metastases being discovered in the lungs. PTs of the breast rarely metastasize to the gastrointestinal tract, and reported cases are scarce. To date, a review of the English literature revealed only 3 cases, including our case, of PTs metastasis to stomach. Case presentation An 82-year-old female patient had 10-year-duration of palpable huge tumor on left breast which was in rapid growth in recent months. Total mastectomy of left breast was performed thereafter, and pathology diagnosis was malignant phyllodes tumor. Adjuvant radiotherapy was suggested while she declined out of personal reasons initially. For PTs recurred locally on left chest wall 2 months later, and excision of the recurrent PTs was performed. She, at length, completed adjuvant radiation therapy since then. Six months later, she was diagnosed of metastasis to stomach due to severe anemia with symptom of melena. Gastrostomy with tumor excision was performed for uncontrollable tumor bleeding. Conclusion For PTs presenting as anemia without known etiologies, further studies are suggested to rule out possible gastrointestinal tract metastasis though such cases are extremely rare. Management of metastatic gastric tumor from PTs should be done on a case-to-case basis, surgical intervention may be needed if there is persistent active bleeding despite medical treatment. Adjuvant radiotherapy is recommended in borderline and malignant PTs with tumor-free margin < 1 cm and high-risk malignant tumors. Adjuvant chemotherapy or target therapy may be helpful for metastatic PTs. Molecular and genomic techniques may predict clinical outcomes of benign and borderline PTs more precisely.